Five-Tier Instrument to Identify Students’ Misconceptions and Representation: A Systematic Literature Review - Rokhim, Deni Ainur; Widarti, Hayuni Retno; Sutrisno, Sutrisno (Orbital: The Electronic Journal of Chemistry, 2024)
Initial knowledge and conception are one of the factors that have a major influence on learning activities. This is the basis for building students’ knowledge of a material concept. However, not all students have the same ability, there are students who have low ability to build concepts. As a result, students who have low ability to build concepts may experience misconceptions that have an impact on their learning outcomes. Therefore, it is necessary to have an appropriate test instrument to identify misconceptions and multiple representation profiles especially in chemistry learning materials, one of which is the topic of reaction rate. This article aims to provide an overview of the application of the five-tier diagnostic instrument in identifying misconceptions and profiles of students’ misconceptions about reaction rates. The method used is the SLR (Systematic Literature Review) from literature studies from 2011 to 2021 which are available in the ERIC, SINTA, and Google Scholar databases. The findings of the research results show that the five-tier test instrument can identify students’ misconceptions about learning material. Information obtained from the use of the instrument can be used to determine the development of students’ ability to understand chemistry using representations.